Calibration and validation for the vessel maneuvering prediction (VMP) model using AIS data of vessel encounters. (1st December 2018) - Shu, Yaqing; Daamen, Winnie; Ligteringen, Han; Wang, Meng; Hoogendoorn, Serge
Abstract: The Vessel Maneuvering Prediction (VMP) model, which was developed in a previous work with the aim of predicting the interaction between vessels in ports and waterways, is optimized in this paper by considering the relative position and vessel size (length and beam). The calibration is carried out using AIS data of overtaking vessels in the port of Rotterdam. The sensitivity analysis of the optimal parameters shows the robustness of the calibrated VMP model. For the validation, the optimal parameters are used to simulate the whole path of overtaken vessels and vessels in head-on encounters. Compared to the AIS data, the validation results show that the different deviations in longitudinal direction range from 33 m to 112 m, which is less than 5% of the waterway stretch. Both the calibration and validation show that the VMP model has the potential to simulate vessel traffic in ports and waterways. Highlights: The VMP model is further developed to predict the interaction between vessels. The overtaking vessels are used to calibrate the VMP model. Sensitivity analysis shows the robustness of the VPM model. The optimal parameters are used to simulate vessels in encounters.